Menampilkan Ya'ahowu Secara Baru Sebagai Salam Liturgis: Menghadirkan Kebertemanan Bagi Pemuda Nias - Eirene Kardiani Gulo; Rasid Rachman (Indonesian Journal of Theology, 2026)
This article addresses the increasingly complex and urgent mental health challenges facing younger generations. In this context, church liturgy is examined not only as a site of ritual practice and faith formation, but also as a pastoral space. The article argues that the liturgical utterance of ya’ahowu (“may you be blessed”) in the Banua Niha Keriso Protestan (BNKP) liturgy has the potential to function as a pastoral resource that strengthens and sustains Nias youth amid mental health-related struggles. Employing a descriptive-qualitative approach, this study draws on BNKP liturgical texts, scholarly discussions of ya’ahowu, liturgical pastoral theology, liturgical inculturation, and youth mental health. These sources are complemented by in-depth interviews with two Nias cultural informants to elucidate the meaning of ya’ahowu, as well as with four Nias Christian adolescents to explore their lived experiences of mental health challenges. The findings suggest that the liturgical practice of uttering ya’ahowu within BNKP worship can affirm a positive communal identity, foster hope, and reinforce a sense of meaningful life among worshippers.